Effects on Bioaccumulation, Growth Performance, Hematological Parameters, Plasma Components, and Antioxidant Responses in Starry Flounder (Platichthys stellatus) Exposed to Dietary Cadmium and Ascorbic Acid - Tae-Jun Won; Young-Bin Yu; Jung-Hoon Kang; Jun-Hwan Kim; Ju-Chan Kang (MDPI AG, 2023)
This study evaluates the toxic effects of dietary Cd and mitigative effects of AsA supplementation by measuring the growth performance, bioaccumulation, hematological parameters, plasma components, and antioxidant responses of Starry flounder (Platichthys stellatus). Platichthys stellatus (mean weight, 69.5 ± 1.4 g; mean length, 18.2 ± 0.21 cm) was fed with dietary cadmium-ascorbic acid (Cd-AsA) composed of C0A0, C0A500, C0A1000, C40A0, C40A500, C40A1000, C80A0, C80A500, and C80A1000 mg of Cd-AsA per kg diet for four weeks. Our results showed that Cd accumulation significantly increased in proportion to the Cd concentration, where the highest levels were observed in the intestine, followed by the kidney, liver, and gills. Dietary AsA significantly mitigated the Cd accumulation in all tissues, and the reduction in Cd accumulation was proportional to the increase in AsA concentration. Dietary Cd has adverse effects on growth performance (body weight gain, specific growth rate, feed conversion ratio, and hepatosomatic index) and can alter the hematological parameters (red blood cell count, hematocrit, and hemoglobin), plasma components (glucose, total protein, glutamic oxaloacetic transaminase, and glutamic pyruvic transaminase), and antioxidant responses (superoxide dismutase, catalase, glutathione S-transferase, and glutathione). Dietary AsA restored the decreased growth performance parameters and the altered hematological parameters, plasma components, and antioxidant responses caused by the dietary Cd exposure. The results of this study showed that dietary Cd is toxic to P. stellatus, while dietary AsA is effective in mitigating the toxic effects of Cd.